Frequency based inductive resonant wireless power transfer for maximum output power efficiency - Ismail Adam (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
Wireless Power Transfer (WPT) has been widely used in recent years for charging electric vehicles, powering gadgets, and activating inaccessible wireless devices. With the variety of existing technologies available, the power transferred to wireless electric vehicles, for example, is no longer an illusion. Inductive resonant technology has gained more popularity compared to their counterpart WPT technologies which are inductive and capacitive because it can transfer power over longer distances more effectively and safely. In inductive resonance, the power transferred to the load is maximized if the WPT link has a high-quality factor (Q) and the load impedance is matched properly to the system output impedance provided the WPT link works at the resonance frequency. The main considerations in inductive resonant WPT are to apply the equivalent circuit theory to the model theoretically and analyze the single load inductively coupled WPT system to ensure it works better at the resonance frequency. Therefore, this research focuses on the technique of how the resonance frequency of the inductive resonant WPT link can be estimated. In this research, the possibility of using total harmonic distortion (THD) in finding resonance frequency under varying link impedance conditions, is investigated. An experimental testbed to estimate the resonance frequency of inductive resonant WPT link was developed. Experimental data were obtained by measuring the transmitted and received voltages and then, analyzing them in the offline mode for THD estimates. The results are validated by calculating and comparing WPT performance using experimental data for relative power delivery in resonance, under-resonance, and over-resonance conditions. It has been shown that at the resonance frequency the power delivery reaches the highest point corresponding to the total harmonics distortion at the lowest peak and root mean square voltage (VRMS) of the transmitted voltage (at the primary coil) at the highest peak. This suggests that the resonance frequency estimation of the inductive resonant WPT link can be implemented automatically and dynamically by measuring the transmitted voltage and finding the lowest THD peak and highest VRMS peak using a specially developed algorithm or intelligent system. It is recorded that, at a distance of 0-5cm, the relative power transmitted to the load is increased by 45% at the estimated resonance frequency compared to the relative power delivered to the load at the best-fixed frequency. The result validated that the higher power is transferred to load provided the estimated resonance frequency is closer to the actual resonance frequency. Thus, it proves that it is possible to estimate the resonance frequency of the inductive resonant WPT link by finding the lowest THD value measured on the transmitter side. Therefore, the resonance frequency estimation for inductive resonant wireless power transfer using total harmonics distortion (THD) was successfully explored and employed in this research.